The Computer Boys Take Over: Computers, Programmers, and the Politics of Technical Expertise. - Agar, Jon (Isis: A Journal of the History of Science in Society, 2011)
A review of the book "The Computer Boys Take Over: Computers, Programmers, and the Politics of Technical Expertise," by Nathan L. Ensmenger is presented.